In Patients Undergoing Cochlear Implantation, Psychological Burden Affects Tinnitus and the Overall Outcome of Auditory Rehabilitation - Brüggemann, Petra; Szczepek, Agnieszka J.; Klee, Katharina; Gräbel, Stefan; Mazurek, Birgit; Olze, Heidi (Frontiers in Human Neuroscience, 2017)
Cochlear implantation (CI) is increasingly being used in the auditory rehabilitation of deaf patients. Here, we investigated whether the auditory rehabilitation can be influenced by the psychological burden caused by mental conditions. Our sample included 47 patients who underwent implantation. All patients were monitored before and 6 months after CI. Auditory performance was assessed using the Oldenburg Inventory (OI) and Freiburg monosyllable (FB MS) speech discrimination test. The health-related quality of life was measured with Nijmegen Cochlear implantation Questionnaire (NCIQ) whereas tinnitus-related distress was measured with the German version of Tinnitus Questionnaire (TQ). We additionally assessed the general perceived quality of life, the perceived stress, coping abilities, anxiety levels and the depressive symptoms. Finally, a structured interview to detect mental conditions (CIDI) was performed before and after surgery. We found that CI led to an overall improvement in auditory performance as well as the anxiety and depression, quality of life, tinnitus distress and coping strategies. CIDI revealed that 81% of patients in our sample had affective, anxiety, and/or somatoform disorders before or after CI. The affective disorders included dysthymia and depression, while anxiety disorders included agoraphobias and unspecified phobias. We also diagnosed cases of somatoform pain disorders and unrecognizable figure somatoform disorders. We found a positive correlation between the auditory performance and the decrease of anxiety and depression, tinnitus-related distress and perceived stress. There was no association between the presence of a mental condition itself and the outcome of auditory rehabilitation. We conclude that the CI candidates exhibit high rates of psychological disorders, and there is a particularly strong association between somatoform disorders and tinnitus. The presence of mental disorders remained unaffected by CI but the degree of psychological burden decreased significantly post-CI. The implants benefitted patients in a number of psychosocial areas, improving the symptoms of depression and anxiety, tinnitus, and their quality of life and coping strategies. The prevalence of mental disorders in patients who are candidates for CI suggests the need for a comprehensive psychological and psychosomatic management of their treatment.